The Empirical Study on Intellectual Capital Approach toward Financial Performance on Rural Banking Sectors in Indonesia - Sidharta, Iwan; Affandi, Azhar (International Journal of Economics and Financial Issues, 2016)
The success of a company in high level competition requires public trust. Similarly, the banking services provider of Rural Banking Sector in Java, Indonesia. To keep customer satisfaction with high trust of financial performance that customer loyalty can be achieved is necessary for public which is measured through financial performance.The aim of this study was to investigate the effect of Intellectual Capital in the banking sector on the island of Java, Indonesia to financial performance. Data processing techniques using Multiple Regression.The research method using purposive sampling and exploratory with a sample number 615. The data were analyzed using Eviews 7 and Microsoft Exel 2007. The results showed that the Value Added Capital Employee (VACA) variables significantly influence toward Financial Performance and Value Added Human Capital (VAHU) variables and variable Structural Capital Value Added (STVA) have significant effect also on toward Financial Performance. The overall test results produced an adjusted R squares indicate that the Intellectual Capital variables significantly influence toward Financial Performance. Keywords: intellectual capital, value creation, firm performance, financial performance JEL Classifications: D83, M21